2022
DOI: 10.1186/s12931-022-02133-3
|View full text |Cite
|
Sign up to set email alerts
|

SINFONIA study protocol: a phase II/III randomised controlled trial examining benefits of guided online group singing in people with chronic obstructive pulmonary disease and interstitial lung disease and their carers

Abstract: Background Chronic obstructive pulmonary disease (COPD) and interstital lung disease (ILD) are incurable conditions characterised by airflow limitation, persisting respiratory symptoms, and progressive respiratory failure. People living with COPD or ILD often suffer from chronic and severe breathlessness, with limited treatment options and low engagement rates with current therapies. Group singing represents a potential community-based therapy to improve quality of life for patients with COPD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…New singing protocols should be developed and refined to include virtual or noncontact methodologies. In this review, two studies used only an online method [23,30], and two other studies applied online and in-person treatment components [22,38]. Unlike in recent medical research, there was no clear infection-related trend in the pulmonary rehabilitation research with singing intervention.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…New singing protocols should be developed and refined to include virtual or noncontact methodologies. In this review, two studies used only an online method [23,30], and two other studies applied online and in-person treatment components [22,38]. Unlike in recent medical research, there was no clear infection-related trend in the pulmonary rehabilitation research with singing intervention.…”
Section: Discussionmentioning
confidence: 95%
“…The most frequently conducted research method was randomized controlled trials (RCT) (n = 12) including one feasibility study [18] and two pilot studies [19,20]. Aside from RCT, there were five one-group pre-post design studies [21][22][23][24][25], three case studies [26][27][28] and descriptive studies including study protocols [29,30], and program evaluation [31,32]. Three qualitative studies were also found [33][34][35].…”
Section: Methodological Approachesmentioning
confidence: 99%
See 2 more Smart Citations